Better breeding research and partnerships enable 43 million farmers to access and grow stress-tolerant maize in sub-Saharan Africa - CGIAR Research Program on Maize (2021)
Rapid-cycle breeding to steadily deliver improved varieties to farmers is essential to adapt maize systems to increasing climate variability. So is varietal replacement linked to a farmer-accessible, competitive seed sector. Investment over the past decade has increased breeding efficiency and varietal replacement. Over 37 million people benefit from new stress tolerant maize varieties, which cover almost 5.5 million hectares in sub-Saharan Africa. These varieties have demonstrated increased yield and yield stability resulting in greater production and improved livelihoods.